Tradisi Meboros Kidang Terkait Pujawali Di Pura Desa Busungbiu Kabupaten Buleleng (Kajian Proses, Nilai, Dan Fungsi): (Kajian Proses, Nilai, dan Fungsi) - Wardika, I Made Arya (Sphatika: Jurnal Teologi, 2026)
The Meboros Kidang Tradition is one of the religious oral traditions that is still preserved and carried out by the people of Busungbiu Village, Buleleng Regency, as an integral part of the Pujawali ceremony series at the Village Temple. This tradition is rooted in the history of the establishment of the Puseh Temple in Busungbiu Village and is passed down from generation to generation as a form of respect for ancestors and a manifestation of devotion to Ida Sang Hyang Widhi Wasa. This study aims to describe the process of implementing the Meboros Kidang Tradition, examine the values ​​contained therein, and explain the social and religious functions of the tradition for its supporting community. The study uses a qualitative approach with data collection methods in the form of interviews and documentation studies, and is analyzed using structural functionalism theory. The results of the study indicate that the Meboros Kidang Tradition has sacred ritual stages, starting from the village paruman, the ngajit ceremony, to the kidang hunting procession which is carried out with strict customary rules. This tradition contains religious, ethical, magical, and belief values ​​that function as a means of purification in both the secular and spiritual realms. Furthermore, the Meboros Kidang Tradition serves to strengthen social solidarity, foster a spirit of mutual cooperation, and strengthen relationships among village communities through the practice of ngayah. Thus, the Meboros Kidang Tradition serves not only as a local cultural heritage but also as a medium for educating religious and social values ​​relevant to the lives of Balinese Hindus.